ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP DENGAN PENDEKATAN MATEMATIKA REALISTIK (PMR) - Juwita, Erie; Kartika, Hendra (De Fermat : Jurnal Pendidikan Matematika, 2025)
Mathematical creative thinking skills are essential for junior high school students to meet 21st-century learning demands, yet many studies show that these skills remain low. This study aims to analyze students’ mathematical creative thinking skills after the implementation of Realistic Mathematics Education (PMR). The research employed a mixed-method approach with an explanatory sequential design using a One Group Pre-test–Post-test model involving 37 eighth-grade students at SMP Negeri 1 Karawang Barat. The normality test indicated that the data were normally distributed (p = 0.095 > 0.05), allowing further analysis with a paired t-test. The results showed a significant difference between pre-test and post-test scores (p = 0.00041 < 0.05) with an effect size of 0.6 (moderate category). Gain analysis using the tertile method revealed that the greatest improvement occurred in the low-ability group (gain = 20), followed by the moderate group (gain = 14), while the high-ability group showed a decrease (gain = –3). Overall, the findings indicate that PMR is effective in enhancing students’ mathematical creative thinking skills, particularly for those with low and moderate initial abilitie.